Alteronol Enhances the Anti-tumor Activity and Reduces the Toxicity of High-Dose Adriamycin in Breast Cancer - Boxue Ren; Boxue Ren; Lei Ye; Jianwei Gong; Huanhuan Ren; Yangfang Ding; Xiaoyu Chen; Xiaona Liu; Peng Lu; Fei Wei; Wenjuan Xu; Qiusheng Zheng; et al. (Frontiers Media S.A., 2019)
The first-line chemotherapy drug adriamycin (ADM) is widely used for the treatment of breast cancer, but the acquired drug resistance and the normal tissue toxicity remain clinical challenges. Alteronol has been reported to exert wide-ranging anti-tumor activity. In this study, we firstly examined the synergistic anti-tumor effects and the underlying mechanisms of alteronol combined with ADM in breast cancer. We have found that the combination of alteronol and ADM significantly suppressed the expression levels of the cell cycle-related proteins (CDC2 and Cyclin B1) and induced cell cycle arrest at the G2/M phase, leading to cell proliferation inhibition in breast cancer 4T1 cells. Moreover, co-treatment of alteronol and ADM (i) remarkably activated p38 and JNK kinases, (ii) elevated ROS levels, (iii) triggered mitochondrial dysfunction, (iv) released cytochrome c into the cytoplasm, (v) upregulated apoptosis-related proteins, e.g., cleaved PARP, Bax, and cleaved caspase-3/9, and (vi) downregulated the expression of Bcl-2, followed by apoptosis. Furthermore, our in vivo studies showed that the low-dose combination of alteronol (2 mg/kg) and ADM (1 mg/kg) significantly inhibited tumor growth in tumor bearing mice, and the anti-tumor effect of the combination was the same as that of high-dose ADM (8 mg/kg). In addition, the low-dose combination group showed lower toxicities to major organs than the high-dose ADM group. Taken together, these data demonstrate that the low-dose combination of alteronol and ADM could notably improve the anti-tumor activity and have lower toxicities to major organs than those in high-dose ADM group.